Sudan : Report on the Final Review of the 2003 Staff-Monitored Program and the 2004 Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2005)
This report examines Sudan's Final Review of the Staff-Monitored Program (SMP) for 2003 and 2004. Policy performance was in line with the program. All quantitative targets, except for that on contracting nonconcessional external debt, were met, and most structural benchmarks were implemented. Sudan made the agreed payment of USD 27 million to the IMF because of high oil prices and strong tax performance. Policy discussions for the 2004 SMP focused on the need to reinforce macroeconomic stability and to provide for post-conflict needs.